The myth of the anti-patriotic conspiracy and the International Masonic Association (Spain, 1921-1975) - Domínguez Arribas, Javier (2020)
This paper focuses on one of the leitmotivs of Spain’s anti-Masonic propaganda: the one which accused the International Masonic Association (IMA) of being responsible for an anti-patriotic conspiracy. After presenting the origins of the Masonic conspiracy myth and highlighting some facts about the real IMA, the use of this  stereotype in the press and in propaganda books over the central decades of the 20th century (1921-75) will be examined chronologically. Furthermore, special attention will be paid to Franco’s actual role in the stigmatisation of the IMA.